Unlocking the potential of banana peel bioactives: extraction methods, benefits, and industrial applications - Khalid Mehmood Wani; M. Dhanya (Discover Food)
Abstract Banana peels, accounting for approximately one-third of the fruit's total weight, are often discarded as waste in the food industry. However, they have long been recognized for their medicinal properties. The bioactive compounds in banana peels are associated with numerous health benefits. This review provides a comprehensive analysis of the valorization of banana peel bioactives, emphasizing extraction methods, bioactive composition, and diverse applications. Extraction techniques, including conventional methods like solvent extraction and maceration, as well as novel technologies such as pulsed electric field (PEF), enzymatic extraction, microwave-assisted extraction, and ultrasound-assisted extraction, are discussed. The review highlights their efficiency in extracting bioactive compounds such as phenolics, flavonoids, carotenoids, and dietary fibers from banana peels. The bioactive composition of banana peels and its health-promoting properties, including antioxidant, antimicrobial, anti-inflammatory, and anticancer activities, are thoroughly examined. Additionally, the review explores various applications of banana peel bioactives in functional foods, nutraceuticals, pharmaceuticals, cosmetics, and agriculture, emphasizing their potential for waste valorization and sustainable development. Therefore, this review offers valuable insights into the utilization of banana peel bioactives, serving as a foundation for further research and industrial implementation across various sectors.